An analytical approach to real-time cloud services on IoT-based applications for smart city planning. (24th December 2021) - Khan, Md. Shahrukh Adnan; Kadir, Kazi Mahtab; Alam, Md. Khairul; Mahmud, Shoaib; Hossain, Shah Reza Mohammad Fahad Ul; Sikder, Md. Pabel; Jefreen, Fiza; Kamal, Ainun
This paper illustrates the cloud-based services on next generation smart living technology, first by providing the concept of smart technology of the next generation, followed by the wide area of application in this sector. Next, the current generation technological enhancement, IoT (Internet of Things) is brought into the smart living. The entire IoT-based Smart Application sector has then been divided into five categories: Power and Energy Sector, Transport Sector, Healthcare Sector, Retail Sector and Education Sector. Each sector has been analysed in detail with respect to possible real-time cloud services, which can be incorporated into the respective area. Consequently, existing cloud services, current trends, limitations and future scopes have been discussed followed by recommendations in each section. For example, for IoT based application in power and energy sector, contribution includes finding the limitations of cloud service have been found such as unoptimised communication scheme, data complexity, interoperability, cyber security risk and data integrity issue. To address these limitations respectively, a policy to ensure backward and horizontal compatibility, proposal to increase local processing, data compression and prediction, implementation of big data techniques, authentication and encryption, planning and redundancy have been included as recommendation. For other four categories, an intense analysis has been carried out in similar fashion. Finally, the recommendation has been added for each category for the next barrier scope of research.